Um problema parabólico com condição de fronteira não-linear e peso indefinido: existência, regularidade, bifurcação e estabilidade de equilíbrios - Madeira, Gustavo Ferron (2008)
This work is concerned with a parabolic problem, occuring in population genetics, under a nonlinear Neumann boundary condition with a weight of indefinite sign and a positive parameter. Considering a phase space appropriate to the physical nature intrinsic to the model, it is proved that the parabolic problem generates a nonlinear dynamical system, which is a gradient system. Therefore, its equilibrium solutions play a fundamental role in the long term dynamics. Then the stationary problem is studied under various aspects: it is proved the existence of a weak equilibrium solution using the variational method; it is established the regularity of weak equilibrium solutions by showing that they are classical ones; the bifurcation and stability structures of equilibria are completely determined. Furthermore the behavior of the trace of the nontrivial equilibrium solution when the parameter is large is established.